›Instrumenta domestica‹ aus Pompeji und ihr Design Eine Untersuchung zur decorativen Gestaltung der Kleinfunde aus Insula I 10 - Hielscher, Adrian (Decorative Principles in Late Republican and Early Imperial Italy (Decor), 2022)
In this book everyday household objects (instrumenta domestica) from the Pompeian Insula del Menandro were used to examine decorative principles, their correlation and interaction. Against a design-theoretical and perception-psychological background, various questions are discussed: How does form support/prevent an easy use? What role plays the material? Where are ornaments and images detectable? Which ornaments and images has been chosen and what is their semantics? Consequently, the focus lies on ancient object design as an expression and part of visual culture. These objects of Roman everyday life reflect cultural knowledge, social norms, values and lifestyles.